Glycemic and Lipedimic Status in Different Trimester of Pregnancy (Bangladesh Journal of Nutrition, 2012)
The study has been undertaken to assess the lipid profile in different trimester of pregnancy. Under a cross-sectional design, 30 healthy nonpregnant as well as 130 pregnant women, at 3 different trimesters of pregnancy (43 in 1st trimester, 44 in 2nd trimester and 43 in 3rd trimester) were sampled for plasma levels of glucose and lipids profile. All the study groups were age matched [mean ± SD; years: 26.02 ± 2.90 in nonpregnant group; 24.95 ± 4.77 in 1st trimester group; 24.36 ± 4.95 in 2nd trimester and 25.49 ± 5.24 in 3rd trimester group respectively]. Plasma total cholesterol, triglyceride, LDL cholesterol and HDL cholesterol level increased throughout the pregnancy. In present study dyslipidemia was found to develop in group with advancing trimester of pregnancy that is the risk of cardio vascular disease. DOI: http://dx.doi.org/10.3329/bjnut.v22i0.12831 Bangladesh Journal of Nutrition Vol.22-23 2009-2010 pp.53-60